All-Solid-State Battery Electrode Sheets Prepared by a Slurry Coating Process. Issue 12 (19th August 2017) - Sakuda, Atsushi; Kuratani, Kentaro; Yamamoto, Mari; Takahashi, Masanari; Takeuchi, Tomonari; Kobayashi, Hironori
Abstract : Some basic but important guidelines for the development of sheet-type all-solid-state batteries using a practical slurry coating process are described in this paper. Li3 PS4 glass powder that had been passed through a 25 μm sieve was prepared. Positive and negative electrode sheets with capacities of more than 1.5 mAh cm −2 were developed. An all-solid-state full cell was constructed using the electrode sheets and the self-standing solid electrolyte sheets. The energy density of the cell was ca. 155 Wh kg −1, where the weight of the current collectors and the exterior package was excluded from the weight for calculation.